Crossword puzzle: a tool for enhancing medical students’ learning in microbiology and immunology - S., Mohan B.; Nambiar, Vinod; Gowda, Shivaraj; Arvindakshan, Rajeev (International Journal of Research in Medical Sciences, 2018)
Background: Incorporation of active-learning methods into classroom allows students to be motivated and enhances their learning experience. Crossword puzzles are found to be an interesting educational tool for teaching medical students as it evokes interest, motivates, enhances their critical thinking, allows a better understanding of concepts, and helps in reinforcing the material acquired during lecture. Aims and Objectives of the research work was intended to implement and evaluate the use of crossword puzzle as a tool in effective learning of Microbiology and Immunology. Methods: Using free online resources, crossword puzzles were created and provided to the students during microbiology and immunology lectures. Students’ perceptions of the crossword puzzle activity were assessed through an 8-item questionnaire using a 5-point Likert scale. The data was collected, tabulated, and statistically analyzed. Results: More than 85% of the students indicated that crossword puzzles enhanced their learning, oriented them to the important topics, and served as good tool in effective learning of microbiology and immunology. Conclusions: Students perceived that crossword puzzles enhanced their learning of microbiology and immunology. Use of crossword puzzles provides a simple, creative, and effective means to incorporate active learning of microbiology and immunology in the classroom.